Sectoral sensitivity of the Kuwait stock market to a dual shock - Talal Alotaibi; Lucía Morales (PLoS ONE, 2025)
This study examines Kuwait’s stock market sectors’ response to the 2020 dual shock of the COVID-19 pandemic and the oil price war between Russia and Saudi Arabia. Traditional cointegration and causality models support the analysis alongside the frequency domain to assess short-run dynamics. The research sample integrates daily data from December 31, 2015, to February 23, 2022. The core research findings indicate that the consumer services, industrials, and basic materials sectors were the most affected by fluctuations in oil prices, highlighting the vulnerability of Kuwait’s oil-dependent economy. Furthermore, the results from the econometric modelling reveal a significant long-run relationship with the West Texas Intermediate index (WTI) and short-run dynamics with the Brent, OPEC and Dubai oil benchmarks. At the global level, monitoring the impact of shocks in commodity-driven economies can help in designing policies that minimise the effects of systemic risks, affecting energy supply chains and inflation stability. This research advances the field by providing a multi-methodological analysis integrating traditional and efficient econometric models to assess sectoral sensitivities in the context of Kuwait, which is an understudied oil-exporting economy. The research findings offer valuable insights for investors and policy-makers in managing risks associated with oil price fluctuations during times of enhanced uncertainty.